Waterfront ecotourism quality evaluation under the water ecological challenge in West Strait, China - Wang, Chengsi; Su, Chenqing; Li, Zhengxin; Hu, Xiaoyin (Frontiers in Environmental Science, 2023)
The relationship between tourism activities and water ecological degradation has become a challenge that cannot be ignored. However, only few studies have evaluated the sustainability of waterfront tourism. This paper takes the West Strait of China, which is rich in ecological resources, as the research object, constructs the evaluation framework of waterfront ecotourism through two rounds of expert consultation, and determines the weights of the following indicators based on Fuzzy Comprehensive Evaluation (FCE): Waterfront Tourism Design (0.112), Ecotourism Experience (0.034), Aquatic Ecological Knowledge Sharing (0.147), Pro-Water Culture (0.238), Pro-Water Identity (0.134), Aesthetic Value of Water Landscape (0.128), Pro-Water City Brand (0.036), Infrastructure Construction (0.061), Regional Economic Development (0.046), Folkway Support (0.028), Government Policy Support (0.036). Data collection in the 5 core cities in West Strait shows that Pro-Water Culture (U4) had the most significant impact, followed by Aquatic Ecological Knowledge Sharing (U3). Pro-Water City Brand (U7) and Folkway Support (U10) have negligible effects on waterfront ecotourism. The weight range distribution is relatively average except for the four above mentioned indicators.